The five - year socio - economic developement plan 2006 - 2010 (Nhà xuất bản Hà Nội, 2006)
The book research aspect: Economic targets, social targets; The environment. Boost the economic growth rate, achieving rapid and sustainable development, quickly bringing our country out of the low development state. Significantly improve people's material, cultural, and spiritual life.